Global events demand global data: COVID-19 crisis responses and the future of selling and sales management around the globe - Rouziou, Maria (2025)
In the context of the global crisis presented by the COVID-19 pandemic, the authors investigate the perspectives of sales managers regarding their organizations’ responses to the crisis and future expectations in a post-COVID-19 world. While there has been much discussion about these topics in the sales literature, very little research has examined them globally by collecting data from many nations and across many continents. Yet, how can global events be understood without analyzing global data? In response, the authors convened the first, to their knowledge, global data coalition by hosting video-recorded group interviews with 76 sales executives representing 27 nations. This inductive investigation, informed by institutional logics, reveals how organizations accepted new norms, retained old ones, or blended the old with the new in response to the crisis. The results simultaneously validate certain emerging concepts on a global scale (e.g., customer success management, bricolage) and give rise to several insights not currently detailed by extant scholarship (e.g., localization, cultural cringe). This work also catalyzes new, relevant avenues for international research and sheds light on issues facing sales practice globally.